1994
DOI: 10.1128/jb.176.16.5131-5134.1994
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression, and nucleotide sequence of the alpha-amylase gene from the haloalkaliphilic archaeon Natronococcus sp. strain Ah-36

Abstract: The alpha-amylase gene of a Natronococcus sp. (1,512 bp) contained a signal peptide of 43 amino acids. Haloferax volcanii expressed the gene and cleaved the signal peptide accurately. The signal peptide shared an extremely high amino acid sequence identity with that of a protease from the halophilic archaeon 172P1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 22 publications
(15 reference statements)
0
27
0
Order By: Relevance
“…The amylases from the mesophilic extremely halophilic Archaea, namely Halobacterium halobium (Good & Hartman, 1970) and Natronococcus amylolyticus (Kobayashi et al, 1992) and the moderately halophilic mesophilic aerobic bacterium Halomonas meridiana (Coronado et al, 2000a) have markedly different enzymic properties and range from being halotolerant enzymes, which are relatively stable and active at low salt concentrations, to extremely halophilic ones, which are inactivated at low salt concentrations. Studies have shown that the enzymes from Halomonas meridiana (Coronado et al, 2000b) and N. amylolyticus (Kobayashi et al, 1994), have significantly elevated levels of acidic amino acids but this characteristic is much more prevalent in the more halophilic N. amylolyticus amylase. In general, the amylase enzymes from mesophilic halophilic organisms may be of limited use in industrial starch-degrading applications as they are not active or stable at high temperatures (above 60 mC).…”
Section: Abbreviation : Dns Dinitrosalicylic Acidmentioning
confidence: 99%
“…The amylases from the mesophilic extremely halophilic Archaea, namely Halobacterium halobium (Good & Hartman, 1970) and Natronococcus amylolyticus (Kobayashi et al, 1992) and the moderately halophilic mesophilic aerobic bacterium Halomonas meridiana (Coronado et al, 2000a) have markedly different enzymic properties and range from being halotolerant enzymes, which are relatively stable and active at low salt concentrations, to extremely halophilic ones, which are inactivated at low salt concentrations. Studies have shown that the enzymes from Halomonas meridiana (Coronado et al, 2000b) and N. amylolyticus (Kobayashi et al, 1994), have significantly elevated levels of acidic amino acids but this characteristic is much more prevalent in the more halophilic N. amylolyticus amylase. In general, the amylase enzymes from mesophilic halophilic organisms may be of limited use in industrial starch-degrading applications as they are not active or stable at high temperatures (above 60 mC).…”
Section: Abbreviation : Dns Dinitrosalicylic Acidmentioning
confidence: 99%
“…strain Ah-36 awaits industrial exploitation. The enzyme exhibits maximal activity at 55°C, pH 8.7 and 2.5 M NaCl and hydrolyzes soluble starch, amylose, amylopectin and also glycogen, producing mainly maltotriose, with glucose and maltose as side products in negligible amounts (Kobayashi et al 1994). Most of the known archaeal pullulanases are Type II enzymes: they attack the α-1,6 glycosidic linkage in pullulan, producing maltotriose or, by α-1,4 glycosidic linkage, panose and isopanose, but they are inhibited by cyclodextrins.…”
Section: Archaeal Enzymes Of Biotechnological Interestmentioning
confidence: 99%
“…Halophilic microorganisms are potential sources of enzymes uniquely adapted to activity at high salt concentrations with application in beverages, pharmaceutical and detergent industries (Kamekura et al 1992; Kobayashi et al 1994;Adams & Kelly 1995;Li et al 2002), leather industry (Birbir et al 1996) and food preservative industries (Ventosa et al 1995;Mellado et al 2003). However, no focused research has been undertaken.…”
Section: Introductionmentioning
confidence: 99%